Influence of annealing temperature on structural, electrical and optical properties of tungsten doped vanadium dioxide thin films by sol-gel spin coating method / Nurul Natasha Saliman - Saliman, Nurul Natasha (2019)
In this project, Tungsten doped with Vanadium oxide thin films was deposited by using sol-gel method, spin coating technique. Vanadium dioxide was selected because of their thermochromic properties that can change optical and electrical properties due to variation of temperature [1]. This ability made it a good material for the smart window application. From previous researcher the doped transition temperature of vanadium dioxide can be in proved by added tungsten [2],[1]. Sol-gel is a method to producing solid material from a chemical. It is the most trustfully liquid phase deposition process for obtain successful result for thin film [3]. Sol-gel is the simplest, cheaper and no complicated process equipment needed to be done. These methods can be used to obtained little tiny result from transparent, nanometer scale. One of the main advantages of sol-gel method was very high accurate in diameter, cross-sectional area and the thickness of layer wall [4]. The precursor was formed by mixing the Vanadium oxide, Tungsten and the isopropanol solution. Quartz substrate was doped with precursor prepared for annealing process. Quartz substrate was selected due to suitable in handling all value including high annealing temperature [5], [6], [7]. 5 sample of quartz substrates needed with size 2cm x 2cm.